2011
DOI: 10.5539/ijbm.v6n4p136
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Spiritual Leadership and Issues of Spirituality and Religiosity: A Study of Top Turkish Managers

Abstract: In recent years, research focusing on intangible issues in business contexts has flourished. The authors of the
current study aimed to contribute to this research by considering managers in terms of their spiritual leadership,
spirituality and religiosity. This study addresses these concepts and tests a model that assesses the relationships
between the spiritual leadership attributes of top Turkish managers and the spirituality and religiosity of those
individuals. The results reveal four k…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 36 publications
4
20
0
3
Order By: Relevance
“…Reave [41] done a review and found that values have been considered spiritual ideals such as integrity, honesty, and humility, have an effect on leadership success. Further research conducted by Ayranci [42] examines the relationship between spiritual leadership and issues of spirituality and religiosity among Turkish managers found that spiritual leadership of Turkish managers depends on their wisdom and unselfishness and their spirituality is comprised of their approach to immateriality and their spiritual awareness.…”
Section: B Leadership Stylementioning
confidence: 99%
“…Reave [41] done a review and found that values have been considered spiritual ideals such as integrity, honesty, and humility, have an effect on leadership success. Further research conducted by Ayranci [42] examines the relationship between spiritual leadership and issues of spirituality and religiosity among Turkish managers found that spiritual leadership of Turkish managers depends on their wisdom and unselfishness and their spirituality is comprised of their approach to immateriality and their spiritual awareness.…”
Section: B Leadership Stylementioning
confidence: 99%
“…Very few studies find out that top managers' spiritual capabilities are partly effective on the business performance (Ayranci, 2010), spirituality and spiritual capabilities are different when top managers are considered (Ayranci & Semercioz, 2011), spiritual leadership features of the family member top managers can affect their family businesses (Dede & Ayranci, 2014), this intelligence is beneficial in the process of transformational leadership development (Hasani, Alam, & Sepasi, 2013), and managers' spiritual capabilities can be used to inspire workers towards organizational goals (Zarei Matin, Kheirandish, & Jahani, 2010). Shortly, spiritual capabilities are important actors of management and leadership.…”
Section: The Significance Of Emotional and Spiritual Intelligencementioning
confidence: 99%
“…However, while Fry's (2003) theory claims universality, as reflected through the universal nature of spiritual assumptions and attitudes, these foundation studies were all conducted in a predominately North American, individualistic cultural context. This trend has changed, as of late, in which reliable studies have begun emerging in diverse cultural contexts with unique spiritual foundations and attitudes, including Turkey (Ayranci & Semercioz, 2011), Pakistan (Bodia & Ali, 2012), Iran (Javanmard, 2012), China (Chen, Yang, & Li, 2012), and South Korea (Jeon, Passmore, Lee, & Hunsaker, 2013). Notably, while these recent studies in culturally and spiritually diverse contexts have both expanded the reach of spiritual leadership and validated its universality, the studies have not investigated the potential underlying role of the cultural context in the emergence of spiritual leadership.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond a North American context, empirical research validating and extending Fry's (2003) spiritual leadership model has emerged in diverse cultural contexts, commencing with an exploratory factor analysis of the relationship between spiritual leadership and religiosity in Turkey (Ayranci & Semercioz, 2011) and a study examining the relationship of spiritual leadership and various demographic factors in Pakistan (Ali et al, 2011). Additional studies include spiritual leadership replication studies in Pakistan (Bodia & Ali, 2012), Iran (Javanmard, 2012), and South Korea (Jeon et al, 2013), and two studies in China that extended Fry's spiritual leadership model to include organizational citizenship behavior as an organizational outcome ) and self-esteem and self-efficacy as mediating variables between spiritual leadership and outcome variables .…”
Section: Introductionmentioning
confidence: 99%